L’alternance codique dans les interactions en classes des Ddnlau collège au Liban - Wajiha Smaili; Dalal Dannoun; Sonia Messai-Farkh (Recherches en didactique des langues et des cultures)
In the private and public Lebanese schools, French (L2) is the language of education of the scientific disciplines from nursery school to university. The disciplinary knowledge must be taught in French and evaluated in L2, which makes the mastery of this language an important factor in the teaching of the disciplines in question. Thenceforth, the linguistic training of the teachers of disciplines called non-linguistic (Ddnl: mathematics, physics, biology, geology, and chemistry) becomes an important component of the professional training of these teachers.Our project is part of the making of a training in French language, for teachers of non-linguistic disciplines taught in Lebanon, including mathematics, physics, biology and chemistry. We started a corpus collection of classroom interactions in classes of the 3rd cycle of the Lebanese educational system (equivalent to middle school in France). The aim assigned to this corpus constitution is the preparation of a training program of “French for Specific Purposes”, in order to help the teachers of non-linguistic disciplines make their courses more interactional.We started from the following fact: the analysis of the discourse of teachers highlighted that physics and mathematics teachers use more frequently their mother tongue, compared to their colleagues in chemistry and biology. We tried to analyze the code-switching in professional linguistic practices used by the teachers, and to determine the causes of this phenomenon.The results of the analysis have showed that the principal language of didactic communication in the lectures of chemistry, biology and geology in French, while the mother tongue is the principal vector of communication in the courses of mathematics and physics. Many forms of practices, inherited from the educational culture, could explain the phenomenon: evaluation practices requiringe further use of the language in chemistry, biology, and geology, a more abstract content in mathematics and physics which leads the teacher to focusing on the transmission of knowledge and to reduce the difficulty by using the L1. The set of results allows us to guide the program of formation in French for specific purposes in preparation